CCL19 and CCR7 Expression, Signaling Pathways, and Adjuvant Functions in Viral Infection and Prevention - Yan, Yan; Chen, Renfang; Wang, Xu; Hu, Kai; Huang, Lihua; Lu, Mengji; Hu, Qinxue (Frontiers in Cell and Developmental Biology, 2019)
Chemokine (C–C motif) ligand 19 (CCL19) is a critical regulator of the induction of T cell activation, immune tolerance, and inflammatory responses during continuous immune surveillance, homeostasis, and development. Migration of CC-chemokine receptor 7 (CCR7)-expressing cells to secondary lymphoid organs is a crucial step in the onset of adaptive immunity, which is initiated by a complex interaction between CCR7 and its cognate ligands. Recent advances in knowledge regarding the response of the CCL19-CCR7 axis to viral infections have elucidated the complex network of interplay among the invading virus, target cells and host immune responses. Viruses use various strategies to evade or delay the cytokine response, gaining additional time to replicate in the host. In this review, we summarize the impacts of CCL19 and CCR7 expression on the regulation of viral pathogenesis with an emphasis on the corresponding signaling pathways and adjuvant mechanisms. We present and discuss the expression, signaling adaptor proteins and effects of CCL19 and CCR7 as these molecules differentially impact different viral infections and viral life cycles in host homeostatic strategies. The underlying mechanisms discussed in this review may assist in the design of novel agents to modulate chemokine activity for viral prevention.